Development of chemical sensors based on tapered optical fiber tip coated with nanostructured thin films - Shabaneh, Arafat Abdallah Abdelwadod (2015)
In this PhD research, novel chemical sensors based on nanomaterial thin films on tapered optical fiber tips were developed and investigated. Nanotechnology enabled chemical sensors have been reported to show better sensing performance as compared to the conventional sensors towards target analytes due to their high surface area. Nevertheless, the previous developments were mostly concentrated on the thick films and electrical based sensors rather than optical based sensors. Therefore, this PhD research project is to explore the sensing potential of the tapered optical sensor and comprehensively study various kinds of nanomaterial thin films as the chemical sensing layers. This was undertaken with the aspirations of enhancing the performance of the nanomaterial thin films based tapered optical fiber sensors as compared to the conventional based sensors. Two of the chemicals frequently utilized in biomedical, chemical and food industries are ammonia (NH3) and ethanol. NH3 is used in the food industries although it is a colorless gas with a strong offensive odor. Some sources of this gas are power plants, chemical industries and fertilizer manufacturing. It can be extremely hazardous to humans if inhaled. On the other hand, ethanol sensors are also widely deployed for health applications such as breath analyzer. Therefore it is important to have a sensing system that can detect the presence and concentration of these chemicals in the environment. In this project, the developed sensor system is tested towards NH3 gas and aqueous ethanol. One of the most suitable optical transducing platforms for sensing applications is tapered optical fiber. In this PhD work, tapered optical fibers were fabricated using Vytran glass processing workstation to achieve tapers with different tip diameters. The tips were coated with different nanomaterials thin films known to be sensitive towards NH3 and ethanol. The nanomaterials under investigation are zinc oxide (ZnO), polyaniline (PANI), graphene oxide (GO) and carbon nanotubes (CNTs). These materials are known to have optical, mechanical and excellent physiochemical properties. However, their potential in optical based chemical sensing applications has yet to be fully explored especially in their nanostructure forms. Optical sensors require a thin catalytic metal layer such as palladium (Pd) or gold (Au) to dissociate the gas molecules into the nanomaterials thin films. The deposition of these catalysts and nanomaterials were done via different deposition techniques such as DC-sputtering, dip coating as well as drop casting. Micro-nano characterization techniques such as FESEM, XRD, EDX, AFM, Raman and UV-vis-NIR spectroscopies were employed to obtain detailed structural properties of these nanomaterials in order to fundamentally understand their functionalities with respect to the optical sensors’ performance. The investigations of the chemical sensing performance of the developed tapered optical sensors were carried out. The nanomaterial thin films were deposited onto the tapered optical fiber tip and tested towards the chemicals using reflectance measurement in a customized chamber. The optical fiber tip was connected to a spectrophotometer system (Ocean Optics) to measure the optical signal. The chamber was connected to mass flow controllers (MFC-Aalborg). The optical sensing mechanism of the molecules and sensing layer interaction of the nanomaterials coated onto the optical fiber tip towards NH3 and ethanol were explained. Furthermore, the NH3 sensing performance was also compared for ZnO and PANI nanostructured thin films with different catalysts (Au and Pd). The sensing performances of these nanomaterials were investigated towards NH3 and ethanol with concentrations 0.25% - 1% and 5% - 80%, respectively. For the first time, tapered optical fiber sensors based on Pd/ZnO and Au/PANI nanostructure thin films which are sensitive towards NH3 with low concentrations 0.25% at room temperature were successfully developed. Au and Pd were proven to be highly efficient in improving the optical response as compared to coated sensors without catalyst. Furthermore, the superior optical response exhibited by the Au/ZnO and Pd/PANI nanostructure thin films towards NH3 has never been reported before and thus, can be considered as a significant contribution to the body of knowledge. This was proven with high sensitivity and fast response of the tapered optical fiber tip 25 µm in diameter. The response and recovery times were 38 s and 55 s for Au/ZnO and 58 s and 80 s for Pd/PANI nanostructured thin films coated fiber tip, respectively. The sensitivity of Au/ZnO coated tapered optical fiber sensor is 70.4/vol% NH3 concentration and has slope linearity of more than 99%. The sensitivity of the Pd/PANI coated tapered optical fiber is shown to be 45.8/vol% NH3 concentration and linearity of 95%. The tapered optical fiber tip sensor with a 50 µm diameter which coated with GO exhibited fast sensing performance by having both response and recovery time of less than 25 s at room temperature. The tapered optical fiber tip (50 µm) coated with CNT nanostructured thin films showed an excellent dynamic performance with both response and recovery time. The response and recovery time are less than 1 minute in the visible spectrum range at room temperature. Finally, this PhD work also included the remote sensing of the developed tapered optical fiber sensors for NH3 and ethanol with a distance of 3 km. the results of the remote sensing experiments are stable and repeatable with low reflectance spectrum as compared to the normal sensor. As a result of this PhD research project, several novel tapered optical fiber tip sensors for NH3 and ethanol sensors based on the nanomaterials thin films were developed and investigated.